Energetické hodnocení budov - Sýkorová, Iva (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Diplomová práce řeší problematiku energetického hodnocení bytového domu v Kyjově. Teoretická část analyzuje legislativní požadavky, praktická část obsahuje energetický audit zděného bytového domu s 9 byty pro 18 obyvatel.

Master´s thesis solves problematic of energy evaluation of residential building in Kyjov. The theoretical part analyzes the legislative requirements, the practical part includes energy audit of brick residential building with 9 apartments for 18 inhabitants.
Energy Auditing of Building
Keywords: bytový dům; energetický audit; energetické hodnocení budov; součinitel prostupu tepla; součinitel tepelné vodivosti; úsporná opatření; residential building; energy audit; energy evaluation of buildings; heat transfer coefficient; thermal conductivity; energy saving measures